Hemorrhagic tonsillitis as a presentation of Kaposi's sarcoma - Tahamara Alcalá Villalón; Dinorah de la Caridad Oliva Venereo; Albadio Samir Pérez López (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Lesions in the oral cavity can be the first clinical evidences of HIV infection. Hemorrhagic tonsillitis should be suspicious of a Kaposi's sarcoma, among other causes. Kaposi's sarcoma (KS) is considered a marker of AIDS in HIV infection, which mainly affects the skin, but often acts upon the mucosa of the oral cavity. Objective: To identify hemorrhagic tonsillitis as a form of presentation of Kaposi's sarcoma associated to HIV. Case presentation: A 22-year-old male patient comes to the doctor´s office complaining of odynophagia and dysphagia. Hypertrophic tonsils of hemorrhagic aspect are observed in the laryngoscopy. Systemic cause is suspected, mainly, an HIV infection.  A clinical onset of AIDS as a result of KS with predominant lesions in the oral cavity including the tonsils is confirmed. Conclusions: The hemorrhagic characteristics of tonsillitis leads to a presumptive diagnostic of HIV infection with a Kaposi's sarcoma occurring predominantly in the oral cavity. Keywords: Hemorrhagic Tonsillitis, HIV, AIDS, Kaposi's sarcoma